Impact of capsule endoscopy on management in patients with established crohn's disease-experience from a single tertiary centre. (13th March 2011) - Kalla, R; McAlindon, M E; Drew, K; Sidhu, R
Abstract : Introduction: Capsule endoscopy (CE) has developed a pertinent role in the management of patients with Crohn's disease, however there is a paucity of literature assessing the long term impact of CE. The study aim was to investigate the utility of CE in a cohort of patients with known Crohn's disease and impact on subsequent management. Methods: Patients with a diagnosis of Crohn's disease referred for CE routinely between 2003 and 2009 were identified. CE was only performed in patients who passed the Patency capsule. Data was collected for demographics, previous investigations, findings at CE and subsequent follow-up. Results: 50 patients with a diagnosis of Crohn's disease underwent CE. There were 36 females with a mean age of 43 years (range 16–76 years). The clinical indications included abdominal pain and diarrhoea (80%) and weight loss (32%). 64% of patients had non-diagnostic small bowel radiology. 72% (n=36) of the patients had colonoscopy prior to CE. 54% (n=15/28) had macroscopic abnormalities at terminal ileum (TI): 33% (n=5/15) with evidence of active Crohn's disease, 33% (n=5) with inactive disease and normal histology in 5 patients. There were no capsule retentions. The mean follow-up period was 30 months (±2 months). CE was diagnostic for active small bowel Crohn's disease in 66% (n=33) with findings of multiple ulcers, oedema and erythema. In 42% (n=14/33) of patients, findings were confined to the distal small bowel, two patients had proximal changes, 1 with mid small bowel changes while in 48% (n=16) the changes were diffuse. On logistic regression, diarrhoea (p=0.033) was predictive of active disease on CE. Management was altered in 60% of patients as a result of CE (n=30). These included the use of anti-tumour necrosis factor in 70% (Infliximab: n=17 and Humira: n=4). Six patients had other therapy which included methotrexate (n=2), azathioprine (n=1), steroids (n=1) and pentasa (n=2). Three patients had repeat histology post-CE. In 17 patients there was no evidence of active disease on CE and three patients of this cohort had repeat TI biopsies confirming quiescent disease histologically. CE was performed to assess for recurrence of disease, postoperatively within 12 months of surgery in 14% (n=7). In these post-op patients, CE was positive in all 7 patients and management was altered in 71% (n=5) post-CE. Conclusion: CE is useful in identifying the presence and extent of activity or evidence of recurrence postresection in patients with established Crohn's disease. CE has a high diagnostic yield and positive impact on patient management in a routine clinical setting. CE also helps to rationalise treatment in those with a normal CE.